Calcium waste as a catalyst in the transesterification for demanding esters: scalability perspective - Anton N. Potorochenko; Konstantin S. Rodygin (Beilstein Journal of Organic Chemistry, 2025)
Esters are valuable compounds in fine organic synthesis and industry. The significant growth in the demand for esters requires the development of scalable production methods. Heterogeneous CaO-based catalysts for the production of esters by transesterification are promising catalytic systems for the production of these desired compounds. In this work, the application of calcium carbide slag, a byproduct of acetylene production, was investigated. The catalyst was obtained by calcination of calcium carbide slag at 600 °C (CS600) and characterized by XRD and FTIR analysis. The transesterification reactions were carried out with primary alcohols, producing fatty acid alkyl esters in 51–99% yields, depending on the alcohols’ nature and catalyst amount (1–10 wt %). The CS600 catalyst demonstrated efficiency in the transesterification of low-molecular-weight esters, medium-chain triglycerides (C9–C12), and lactones, resulting in the corresponding methyl esters in 66–99% yields in the presence of low catalyst amounts of 1–5 wt %.